Kelarutan Zat Warna Organik dalam Gelasi Mikroemulsi Water In Oil Sistem dari Air Triton X-100 dan Sikloheksana - Mery Khasanah; Ananda Putra (Departemen Kimia FMIPA UNP, 2021)
Abstract —solubility of dyes from organic matter powder of dragon fruit peel of blue telang flower and turmeric in the gelation of water in oil mikroemulsion of the system of water (pH 4,5 and pH 9,5), Triton X-100, cyclohexane and its application for ink. For water pH 4,5 (controlled by nitric acid) and water pH 9,5 (controlled by potassium hydroxide), the formation of gel from water in oil microemulsion was crieddent using the so-gel mhetod by Tetraethylorthosilicate (TEOS) which underwent hydrolysis with water for from a gel. It was indicated that the solubility of the dye from organic matter in the gelation of water in oil microemulsion is at pH 9,5 dragon fruit peel powder at 0,0215 and the lowest pH 4,5 powder of blue telang flower powder is 0,0120Keywords — solubility, organic dyes, gel, water in oil microemulsion, ink.